The Byzantine Silver Bowls in the Sutton Hoo Ship Burial and Tree-Worship in Anglo-Saxon England - Michael Bintley (Papers from the Institute of Archaeology, 2011)
The ten Byzantine silver bowls included amongst the grave goods interred in the chamber of the Mound 1 ship burial at Sutton Hoo remain one of the most puzzling features of this site. It has been suggested that these items, which lay separated from the rest of the silver in the burial and close to the head of the body-space (where no body was found), may have had some special meaning which has never been discovered. This paper will argue that one of the possible keys to unlocking their significance may be found in the central roundel that adorns the centre of each bowl in the form of a rosette. These bowls, which are thought to have been manufactured in the eastern provinces of the Byzantine Empire in c. 600, entered the British Isles in unknown circumstances before coming into the possession of the man buried in (or commemorated by) the Mound 1 burial. Through comparison with contemporary sculpture and vernacular literature, I will suggest that this central rosette, which was associated with both the cross of Christ and sacred trees in Byzantine sculpture, may have served as a conventional bridge between Christian and pre-Christian religious traditions associated with sacred trees in Anglo-Saxon England. The central rosettes adorning each of these bowls may have been understood as the flower of a sacred tree. Since the latter appears to have figured in Anglian paganism it is possible that the bowls may helped to convert the Anglian aristocracy, bridging a gap between Germanic insular religious traditions and those that were being introduced to Britain at the time that the ship burial itself took place.
Keywords: tree worship; Anglo-Saxon